Pervasive computing paradigms for mental health : 5th International Conference, MindCare 2015, Milan, Italy, September 24-25, 2015, Revised selected papers /: 5th International Conference, MindCare 2015, Milan, Italy, September 24-25, 2015, Revised selected papers. (2016) - Unknown
No abstract available